2007
DOI: 10.1158/0008-5472.can-06-2484
|View full text |Cite
|
Sign up to set email alerts
|

M3 Muscarinic Receptor Antagonists Inhibit Small Cell Lung Carcinoma Growth and Mitogen-Activated Protein Kinase Phosphorylation Induced by Acetylcholine Secretion

Abstract: The importance of acetylcholine as a neurotransmitter in the nervous system is well established, but little is yet known about its recently described role as an autocrine and paracrine hormone in a wide variety of nonneuronal cells. Consistent with the expression of acetylcholine in normal lung, small cell lung carcinoma (SCLC) synthesize and secrete acetylcholine, which acts as an autocrine growth factor through both nicotinic and muscarinic cholinergic mechanisms. The purpose of this study was to determine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
127
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(139 citation statements)
references
References 47 publications
10
127
2
Order By: Relevance
“…It has been reported that cholinergic stimulation leads to cell proliferation through MAPK and Akt pathways. 27,33 In this study, in parallel with stimulation of A549 and PC9 cell proliferation by either carbachol or pilocarpine, phosphorylation of MAPK and Akt was increased ( Fig. S2 and S3).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…It has been reported that cholinergic stimulation leads to cell proliferation through MAPK and Akt pathways. 27,33 In this study, in parallel with stimulation of A549 and PC9 cell proliferation by either carbachol or pilocarpine, phosphorylation of MAPK and Akt was increased ( Fig. S2 and S3).…”
Section: Discussionsupporting
confidence: 57%
“…26 In SCLC, tumor growth has been associated with stimulation of M3 mAChR through mitogen-activated protein kinase (MAPK)-dependent mechanisms. 27 M3 mAChR antagonists can inhibit SCLC growth in vitro and in vivo. In NSCLC, very little is known about which subtypes mediate the proliferative effects of muscarinic activation.…”
Section: Introductionmentioning
confidence: 98%
“…Recently chronic stress and other behavioral conditions have been reported to cause promotion and progression of cancers; catecholamines in ovarian cancers [21,22], muscarinic cholinergic receptors in prostate [23], colon [24], mammary carcinoma cells [25,26], and the receptors and ligands in small cell lung carcinoma [27,28] were shown to promote their growth and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Vukelic et al showed that cholinergic neurotransmitters (ACh), similar to those released through activation of a neural reflex, regulate responses to products of the adaptive immune system, specifically immune complex (IC)-mediated activation of effector cells (31). In particular, in both lung cancer and colon cancer, ACh acts as an autocrine growth factor for cancer growth and development (32)(33)(34). Since cancer cells both produce ACh and express nAChRs, these receptors are believed to be involved in tumorigenesis, even without stimulation with nicotine.…”
Section: Discussionmentioning
confidence: 99%